Tindak Pidana Pencemaran Nama Baik dan Penghinaan melalui Media Pers dalam Perspektif Hukum Pidana di Indonesia - Situmorang, Lasyohana; Aulia, Mega; Amalia, Herni; Audi, Ghita (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
The crime of defamation continues to escalate in Indonesia, particularly with the rapid advancement of globalization and digital media. Instead of diminishing, defamatory acts especially those committed through internet-based platforms and the press have become increasingly prevalent. This study aims to analyze the criminal offense of defamation and insult through the lens of Indonesian criminal law, particularly when disseminated via the mass media. Utilizing a normative juridical approach, the research relies on secondary data sources, including legislation, legal doctrines, scholarly literature, and official documents. The study finds that existing legal instruments often struggle to adapt to the fast-paced evolution of digital communication, particularly in cyberspace, where jurisdictional complexities and evidentiary challenges hinder effective law enforcement. Furthermore, defamatory acts conducted without the victim’s consent not only contravene prevailing legal norms but also violate the values and social customs upheld by local communities. The study highlights the importance of legal reform and the need for responsive legal mechanisms that balance freedom of expression with the protection of individual dignity in both physical and digital spaces.